The same explosive attitude again - Abd Razak, Dzulkifli (2009)
AT the Strasbourg Town Hall meeting in France in April, United States President Barack Obama declared his intention to "seek the goal of a world without nuclear weapons". Contrary to proclamations and pledges over the years since America dropped that bomb over Hiroshima on Aug 6, 1945, what we see today is the converse: nuclear proliferation and armament instead.